Histological and Histochemical Study of Some Lingual Papillae in Male Indigenous Camel Camelus dromedaries - Kadhim, Ammer Ali; Kadhim, Khalid Hadi (Medical Science Journal for Advance Research, 2024)
Background:The goals of this study are to illustrate the properties of lingual papillae of camel. Twenty two tongue specimens for light and scanning electron microscopes. Results were demonstrated that the tongue was 62.31 ± 0.23 cm in length and was gray in color, with a sharp rounded cranial edge and tip flattened like a spatula and had a median groove, tongue was composed of apex, body, and root. Filiform, fungiform, conical, lenticular, and vallate papillae were lingual papillae. Filiform papillae were soft horny threadlike that were many, long, and thin; distributed on dorsal, lateral, and ventral sides of tongue and lined with keratinization stratified squamous epithelium, The fungiform papillae were spherical, convex, mushroom-like dispersed over the dorsal and ventral margins of tongue and were bordered by keratinized epithelium. Conical papillae with a circular base and a blunt tip were toward torus linguae lined with keratinized stratified epithelium. The lenticular papilla was convex lenses in the middle of torus linguae that varied in size and were covered by a keratin layer, Vallate papillae round on lateral side of torus linguae, four in each side, had a V shape, irregular surfaces, covered by a cornified surface. The PAS were positive for Weber’s gland, while negative for Von Ebner’s gland. In conclusion: The morphology of the tongue, as well as the quantity, distribution, and properties of papillae, were found to be connected to diet and feeding patterns, the histological structures of the lingual papillae were similar to those of other ruminants.